56th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2015
DOI: 10.2514/6.2015-1129
|View full text |Cite
|
Sign up to set email alerts
|

Aerostructural Design Optimization of an Adaptive Morphing Trailing Edge Wing

Abstract: Adaptive morphing trailing edge technology offers the potential to decrease the fuel burn of transonic transport aircraft by allowing wings to dynamically adjust to changing flight conditions. Current aircraft use flap and aileron droop to adjust the wing during flight. However, this approach offers only a limited number of degrees of freedom, and the gaps in the wing created when using these devices introduce unnecessary drag. Morphing trailing edge technology offers more degrees of freedom, with a seamless i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Using Eqs. (7) and (8) in Eq. (9) for steady level flight with any spanwise-symmetric lift distribution, and enforcing the assumption that the proportionality constant is spanwise invariant gives…”
Section: A Prandtl's Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Eqs. (7) and (8) in Eq. (9) for steady level flight with any spanwise-symmetric lift distribution, and enforcing the assumption that the proportionality constant is spanwise invariant gives…”
Section: A Prandtl's Formulationmentioning
confidence: 99%
“…Because of the high computational costs of CFD and FEA, significant effort has been made to develop methods that decrease computation time without sacrificing fidelity. [2][3][4][5] High-fidelity methods are generally used for detail-level design of all aircraft, 6 but are sometimes used at the conceptual and preliminary design levels for unconventional geometries and structures, such as morphing trailing edge wings 7,8 and tow-steered wings. 9,10 Although high-fidelity methods have seen significant reductions in computational time, they still carry heavy computational requirements.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effectiveness of a morphing trailing edge device in reducing the fuel burn of a commercial transport aircraft, we performed a number of multipoint aerostructural optimizations using the tools outlined in Section II. We previously performed single point aerostructural optimizations with and without a morphing trailing edge [11]. That work showed limited improvements with the addition of a morphing trailing edge, as the non-morphing wing had nearly optimal for that single flight condition.…”
Section: Multipoint Aerostructural Optimizationmentioning
confidence: 99%
“…Wakayama et al [10] found similar results in theri work considering morphing devices on three different aircraft configurations. The authors previously used high fidelity coupled aerostructural optimization to evaluate a wing with a morphing trailing edge at a single cruise point [11]. That work showed the ability of the morphing trailing edge to drastically effect the wing's lift distribution, but in this work we seek to build off of these previous results by expanding the number of flight conditions where the performance of the wing is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The variable span morphing wing provides an excellent capacity for achieving multiple tasks (10) . By changing the span length and wetted area, the wing addresses numerous mission segments such as cruising, loitering, long flight range, manoeuverability, and controllability, more efficiently than a conventional wing (8,11,12) . Another advantage of adaptive span wing is the roll control through asymmetric wing changes rather than through conventional control surface.…”
Section: Introductionmentioning
confidence: 99%